Pengembangan Sistem Informasi Konversi Kelapa di Kabupaten Indragiri Hilir-Riau - Adhiva, Jeni; Mustakim, Mustakim; Suryani, Penti (Building of Informatics, Technology and Science (BITS), 2021)
Coconut plants are very much found throughout Indonesia, especially located in Riau province, making coconut plantations an economic base, the largest coconut plantation area to be precise in Indragiri Hilir Regency which has a coconut plantation area of 501,576 hectares. The contribution of coconut plantations in Indragiri Hilir makes Indonesia as a whole as the center of the largest coconut plantations in the world. The majority of Indragiri Hilir people work as farmers. The lack of knowledge and understanding of farmers regarding the management and utilization of coconut production is one of the reasons for the lack of coconut processing business in Indragiri Hilir Regency. It is necessary to have information related to the processing of coconut derivative products. This of course can be an illustration to farmers about the benefits that farmers get when selling coconuts that have been processed into products. Based on the results of ICT Literacy processing, 83% was obtained, this shows that post-harvest information is very important about the processing and utilization of coconut plants. Therefore we need an information system that can provide information about the use or management of coconut plants and the conversion of coconut derivatives in Indragiri Hilir district.